Postural deviations in Romberg’s Test in girls with scoliosis and scoliotic posture - Wilczyński, Jacek; Dworakowska, Danuta; Bieniek, Katarzyna; Jascaniniene, Nijole (Akademia Wychowania Fizycznego w Poznaniu)
The aim of the research was to analyze postural deviations in Romberg’s Test in girls with idiopathic scoliosis and scoliotic posture. 28 girls aged 7-18 years old were involved in the study. Spine research was made by Exhibeon digital radiography. Based on the size of the angle of spinal curvature there were identified scoliotic posture: 1-9° and scoliosis: ≥ 10°. Postural reactions were examined by static-dynamic Tecnobody’s ST 310 Plus Stability System platform. There were 21 (75%) children with scoliotic posture, and 7 (25%) with idiopathic scoliosis. Postural reaction of FBSD was from 6.57 with opened eyes (OE) to 7.32 with closed eyes (CE). Postural reaction of MLSD was from 3.89 with opened eyes (OE) to 5.54 with closed eyes (CE). Postural reaction of AFBS was from 11.96 with opened eyes (OE) to 17.29 with closed eyes (CE). Postural reaction of AMLS was from 9.96 with opened eyes (OE) to 13.89 with closed eyes (CE). Analysis of variance with dual classification revealed a significant effect in Romberg’s Test options (OE/CE) to: Average COP X (p = 0.002264), Average COP Y (p = 0.000009), Perimeter (p = 0.000008), Ellipse Area (p = 0.029882), Medium-Lateral Standard Deviation X (p = 0.022162), Average Forward-Backward Speed Y (p = 0.000071) and Average Medium-Lateral Speed X (p = 0.000916). In the examination with eyes closed it has been observed a significant increase of this variances. There was no significant effects only in Forward-Backward Standard Deviation Y. Most of postural deviations did not fit the norm.
Keywords: postural deviations; scoliosis and scoliotic posture; Romberg’s Test; Plus Stability System platform; Exhibeon digital radiography